Self-reported questionnaires to assess indoor home environmental exposures in asthma patients: a scoping review - Dhanusha Punyadasa; Nicola J Adderley; Gavin Rudge; Prasad Nagakumar; Shamil Haroon (BMC, 2024)
Abstract Background The indoor home environment plays a crucial role in determining the outcome of respiratory diseases, including asthma. Researchers, clinicians, and patients would benefit from self-reported questionnaires to assess indoor home environmental exposures that may impact on respiratory health. Objective To review self-reported instruments for assessing indoor home environmental exposures in asthma patients and to characterise their content, development, and psychometric properties. Design A scoping review was conducted with content assessment. Methods A literature search was conducted in Embase and PubMed using the key words housing quality, questionnaire and asthma and their index terms, covering articles published in English between January 2000 to July 2023. Articles in which questionnaires or single item questions were used to assess indoor home environmental exposures in asthma patients in middle- and high-income countries were included. We excluded articles in which the questionnaire required an interviewer or onsite observations and those conducted in low-income countries. Results We screened 1584 articles to identify 44 studies containing self-reported questionnaires measuring indoor home environmental exposures. 36 studies (82%) were cross sectional, 35 (80%) had a sample size of greater than 1000 participants, and 29 (66%) were conducted in children. Most studies (86%, n = 38) had binary (yes/no) or multiple-choice responses. 25 studies (57%) included a recall period of 12 months. 32 studies (73%) had a response rate of greater than 50%. Dampness, biological exposures (e.g. mould), and second-hand tobacco smoke were the most assessed indoor home environmental exposures. Childhood asthma (54%, n = 24) and asthma symptoms (36%, n = 16) were the most examined asthma related outcomes. The exposure most associated with adverse asthma outcomes was exposure to damp (79%, n = 35). 13 studies (29%) had developed a self-reported instrument by adapting questions from previous studies and almost all instruments (n = 42 studies, 95%) had not been validated. Conclusions The scoping review did not identify a comprehensive, validated self-reported questionnaire for assessing indoor home environmental exposures in patients with asthma. There is need to develop and validate a robust but pragmatic self-reported instrument, incorporating the findings from this review.